2006
DOI: 10.1017/s0952523806233078
|View full text |Cite
|
Sign up to set email alerts
|

Achromatic parvocellular contrast gain in normal and color defective observers: Implications for the evolution of color vision

Abstract: The PC pathway conveys both chromatic and achromatic information, with PC neurons being more responsive to chromatic (L-M) than to achromatic (L+M) stimuli. In considering the evolution of color vision, it has been suggested that the dynamic range of chromatic PC-pathway processing is tuned to the chromatic content of the natural environment. Anomalous trichromats, with reduced separation of their L- and M-cone spectral sensitivities, have diminished chromatic input to PC-pathway cells. Dichromats, with absent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
(19 reference statements)
1
5
1
Order By: Relevance
“…The results of our study support earlier studies that found enhancement in various visual functions in X-linked color-defective individuals (Jägle et al, 2006; Sharpe et al, 2006) and also contradict the only known study that addressed almost exactly the same issue (Lutze et al, 2006). In this case, achromatic CS was found to be enhanced in dichromatic observers, especially at higher spatial frequencies.…”
Section: Discussionsupporting
confidence: 88%
“…The results of our study support earlier studies that found enhancement in various visual functions in X-linked color-defective individuals (Jägle et al, 2006; Sharpe et al, 2006) and also contradict the only known study that addressed almost exactly the same issue (Lutze et al, 2006). In this case, achromatic CS was found to be enhanced in dichromatic observers, especially at higher spatial frequencies.…”
Section: Discussionsupporting
confidence: 88%
“…Although there are increasing signs of short-term plasticity, specifically contrast adaptation, at these early stages, [54][55][56] contrast adaptation is known to be substantially stronger in the visual cortex, 36 especially within the parvocellular pathway, along which the L versus M signals are carried. 54,57 The adjustments we measured could potentially represent a very long-term form of visual plasticity, though we cannot rule out a process that acts more rapidly. Color vision adjusts to changes in the environment or observer over widely varying timescales, 58 and compensation for the color losses could similarly involve multiple timescales and processes.…”
Section: Discussionmentioning
confidence: 97%
“…The emergence of compensation in the cortex would mean that the retina and LGN remain in a weakened, unadjusted state for processing the L vs M signals. While there are increasing signs of short-term plasticity, specifically contrast adaptation, at these early stages [54][55][56], contrast adaptation is known to be substantially stronger in the visual cortex [36], especially within the parvocellular pathway along which the L vs M signals are carried [54,57].…”
Section: Discussionmentioning
confidence: 99%